Credit Misallocation During the European Financial Crisis - Fabiano Schivardi; Enrico Sette; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2017)
Do banks with low capital extend excessive credit to weak firms, and does this matter for aggregate efficiency? Using a unique data set that covers almost all bank-firm relationships in Italy in the period 2004-2013, we find that, during the Eurozone financial crisis: (i) Under-capitalized banks were less likely to cut credit to non-viable firms. (ii) Credit misallocation increased the failure rate of healthy firms and reduced the failure rate of non viable firms. (iii) Nevertheless, the adverse effects of credit misallocation on the growth rate of healthier firms were negligible, and so were the effects on TFP dispersion. This goes against previous inuential findings that, we argue, face serious identification problems. Thus, while banks with low capital can be an important source of aggregate inefficiency in the long run, their contribution to the severity of the great recession via capital misallocation was modest.
Keywords: D23; E24; G21; 330; bank capitalization; zombie lending; capital misallocation